The Effects of Diagnosis-Related Groups Policy on Medical Care System Sustainability in China - Qi Hu; Yue Lei; Xiangdan Piao (SAGE Open)
The well-organized medical security system plays an important role in improving public health. This study investigates the effect of the diagnosis-related groups (DRG) policy, which is a way to control cost, on medical care services, including hospital revenue status. Based on the panel data on derived from public medical institutions in Sanming City from 2014 to 2022, the average length of stay for discharged patients, number of admissions per 100 visits, and bed utilization rate were used to measure medical services status. The difference-in-difference method was used to explore the impact of the DRG policy implementation on the overall hospital operation in medical care services in Sanming City, China. We found the DRG policy introduction has a negative effect on the average length of stay for discharged patients, emergency admissions per 100 visits, and the hospital bed occupancy rate. On the contrary, the DRG policy reduces the total medical revenue in terms of the reduced drug revenue. However, the DRG policy increases the examination and the test income, average charge per emergency visit, and drug cost per discharged patient. In sum, the introduction of the DRG policy reduces the medical care system operating cost by reducing drug revenue and bed occupancy, reducing the length of hospitalization, worsening hospital revenue, and increasing the charge for examination and test, emergency visits, and drug cost per discharge. The C-DRG policy implementation in Sanming city effected improvements in public health and overall medical care system services.